2014
DOI: 10.1080/15321819.2014.885448
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Soluble Supramolecular FN-fibrin Complexes in Human Plasma

Abstract: SDS-agarose FN immunoblotting of 257 normal and pathological human plasma samples revealed the ladder pattern of multiple plasma FN bands which corresponded to FN monomer and dimer, and 5 FN-fibrin bands with increasing molecular masses. The FN-fibrin bands of about 750 kDa, 1000 kDa, 1300 kDa, 1600 kDa, and 1900 kDa appeared more frequently and in significantly higher relative amounts in the pathological samples (P < 0.000) than in relatively healthy individuals. The revealing of high-molecular FN-fibrin comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(41 citation statements)
references
References 34 publications
1
40
0
Order By: Relevance
“…We have previously shown that the FN-fibrin complexes, particularly those with lower molecular masses of $750 kDa and $1000 kDa, can occur in some normal samples taken from physically healthy individuals and having normal biochemical and haematological parameters. 15 Whilst RRI can cause either acute, chronic or transitional destruction states of the structure of the respiratory epithelium, our results show the molecular consequences of respiratory infections at the level of activation of inflammatory and coagulation systems. The occurrence of a 280-kDa FN-fibrin reduced form and multiple FN-fibrin complexes seems to be a dynamic and transient process related to pathophysiological events probably connected with normal haemostasis.…”
Section: 17mentioning
confidence: 87%
See 4 more Smart Citations
“…We have previously shown that the FN-fibrin complexes, particularly those with lower molecular masses of $750 kDa and $1000 kDa, can occur in some normal samples taken from physically healthy individuals and having normal biochemical and haematological parameters. 15 Whilst RRI can cause either acute, chronic or transitional destruction states of the structure of the respiratory epithelium, our results show the molecular consequences of respiratory infections at the level of activation of inflammatory and coagulation systems. The occurrence of a 280-kDa FN-fibrin reduced form and multiple FN-fibrin complexes seems to be a dynamic and transient process related to pathophysiological events probably connected with normal haemostasis.…”
Section: 17mentioning
confidence: 87%
“…As discussed earlier, 15 these FN-fibrin complexes differed from the adjacent one by $280 kDa, which corresponded to the mass of one Note: The FN reduced forms (240 kDa and 280 kDa) were detected by Western immunoblotting (Figure 1). RRI groups were stratified as described in legend to Table 1 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations